Bioactivities of selected lichens / Luqman Saidi - Saidi, Luqman (2018)
The aim of this study is to investigate in vitro free radical scavenging, antimicrobial, cytotoxicity and anticancer activities of the methanol and acetone extracts of the lichens Ramalina sp., Usnea sp., Heterodermia sp., and Telochistes sp. Free radical scavenging activity was evaluated by DPPH radical scavenging assay. Of the lichens tested, both acetone and methanol extracts of Ramalina sp. had highest free radical scavenging activity (72.27 %) and (84.43 %) of inhibition at a concentration of 1mg/ml, respectively, which are nearly as potent as the standard antioxidants controls; ascorbic acid (96.45%), trolox (91.9 %), and BHA (94.44 %).